Neospora caninum-associated abortions in cattle from Southern Brazil: Anatomopathological and molecular characterization - da Costa L.S.* (2022)
© 2022 Elsevier B.V.This study aimed to evaluate the N. caninum associated abortions in cattle in the state of Santa Catarina, in the southern Brazil. Aborted bovine fetuses were necropsied, submitting organ samples for histopathological evaluation. Brain fragments were analyzed by polymerase chain reaction (PCR). The diagnosis of abortion due to N. caninum was established through histopathology and molecular analysis in 53.84% (28/52) of the cases, with PCR detection in 71.42% (20/28). The histopathological evaluation showed lesions in 75% of the cases, characterized by mononuclear necrotizing encephalitis, mononuclear myocarditis, mononuclear myositis, mixed placentitis, and mononuclear pneumonia. Neospora caninum was the primary etiological agent associated with causes of abortion in cattle in the present study.